Gioco ingegno utopia. Automata sonori nel mondo greco romano. Alcuni spunti di riflessione - Francesca Berlinzani (Lanx, 2013)
The paper collects the greek and latin testimonies on real or fictitious acoustic automata. The words and the meanings concerning the automatic devices have been considered and analysed, together with the most important personalities of engineers and inventors, in order to determine and single out the possible connections between their creations and the social, political and economic systems that gave impulse to this creative impetus. The analysis tries also to point to the ludic aspects of this process, in which abstraction, epistemological mechanisms, empiric praxis, go together and alternate themselves in a game played between the inventor and his public, a game made of secrets, enigmas, discoveries and acknowledgement, in order to obtain concrete objects that share many aspects with the toys.